Gradação funcional com vidro experimental em coroas implantossuportadas de zircônia: comportamento mecânico e biológico em estudo clínico controlado randomizado e translacional - Ribeiro, Amanda de Oliveira Pinto [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Glass infiltration of zirconia was developed with the aim of enhancing its mechanical strength and enabling indirect restorations without the need for porcelain veneering. By promoting smooth transitions in material properties and incorporating a superficial glass layer, this approach seeks to reduce the risk of delamination and fracture. In addition, antimicrobial agents can be incorporated into the glass powder composition, which may be highly advantageous given that biological complications such as caries, periodontitis, and peri-implantitis have been reported in clinical studies involving ceramic crowns. In this study, the use of an experimental glass infiltration technology was evaluated in implant-supported ceramic restorations. The objective was to assess how the glass gradation process in ultra-translucent zirconia (5Y-PSZ) implant-supported crowns influences clinical prognosis when compared with implant-supported crowns finished with a commercial glaze. Based on predefined inclusion criteria and after obtaining informed consent, patients were selected to undergo osseointegrated implant placement, totaling 57 implants. After the osseointegration period, implant uncovering, provisional restoration fabrication, intraoral scanning, and installation of screw-retained zirconia crowns were performed. Patients were randomly allocated into two groups: ultra-translucent zirconia with commercial glaze (GC) and ultra-translucent zirconia with experimental glaze (GE). Additional groups included provisional restorations (P) and natural teeth as controls (D). Crown and antagonist tooth wear were assessed using GOM Inspect software, color stability was evaluated using a VITA Easyshade® V spectrophotometer, immunological analysis was performed by ELISA, and clinical parameters and subgingival biofilm were analyzed by Checkerboard DNA–DNA hybridization for the GC, GE, P, and D groups at the following time points: provisional phase (−T), 7 days after crown installation (T0), 3 months (T1), 6 months (T2), 9 months (T3), and 12 months (T4). No statistically significant differences in wear were observed among the groups at any time interval, indicating comparable performance of the experimental glaze (GE), commercial glaze (GC), and antagonist enamel (E). Higher concentrations of MMP-8 were observed in the provisional group compared with natural teeth, whereas no statistically significant difference was found for IL-6. At T0 and T1, no significant differences were detected in MMP-8 or IL-6 expression between the tested glazes. When compared with natural teeth, GC showed lower MMP-8 concentration at T0 and became comparable over time (T1). In contrast, GE was statistically similar to natural teeth at both T0 and T1 and also comparable to GC at these time points. For IL-6, only the commercial glaze group showed an increase in concentration over a 6-month period. TNF-α expression was not detected. Cervical fractures occurred in two GE crowns, one after T0 and another between T3 and T4, as well as one fracture of the Ti-base component between T2 and T3. No statistically significant differences in color stability were observed between GC and GE at T0 and T1. At T0, biofilm percentage was similar between the tested glazes and significantly lower than that observed on natural teeth. At T1, no supragingival biofilm was detected on any crown. Mean probing depth values were similar between the crown groups and significantly higher than those of natural teeth at both T0 and T1. Keratinized tissue height and distal papilla width were similar between GE and GC. Checkerboard analysis at T0 showed no significant differences between GC and GE in terms of prevalence or bacterial levels. At T1, Staphylococcus epidermidis exhibited higher frequency and levels in GE than in GC, while Lactobacillus spp. showed higher frequency in GC than in GE, with natural teeth being similar to GE. At T2, Mitis streptococci, Milleri streptococci, Prevotella spp., Porphyromonas gingivalis, Lactobacillus buccalis, and Candida albicans showed higher frequency in GE than in GC, whereas Treponema denticola and Actinomyces spp. were more frequent in GC. Treponema socranskii demonstrated a reduction in prevalence in the GC group over 6 months. At T2, Mitis streptococci, Milleri streptococci, L. buccalis, Eubacterium spp., C. albicans, and Clostridioides difficile exhibited higher bacterial levels in GE compared with GC. Over time (T0–T2), T. socranskii and Lactobacillus spp. increased significantly in the GC group. Overall, zirconia crowns with experimental glass infiltration demonstrated clinical, biological, and esthetic performance comparable to that of commercial glaze, with no significant differences in wear, color stability, or early inflammatory cytokine expression. The experimental glaze behaved similarly to natural teeth across multiple parameters, without significant differences in inflammatory response or wear behavior, whereas the commercial glaze showed an increase in IL-6 over time. Submucosal microbiota differed among crown types and natural teeth, with the experimental group showing greater similarity to natural dentition. Although fractures occurred in both zirconia groups, the novel material exhibited promising mechanical and microbiological behavior, suggesting that glass coating and functional gradation represent a viable alternative for improved implant-supported zirconia restorations.

A infiltração de vidro em zircônia surgiu no intuito de torná-la ainda mais resistente e iniciar um caminho para restaurações indiretas sem a necessidade de estratificação com porcelana permitindo que, com suaves transições de propriedades do material e uma camada superficial de vidro, evitem-se delaminações e fratura. Ainda, é possível incluir agentes antimicrobianos na composição do pó de vidro. Essa adição pode ser altamente vantajosa, uma vez que complicações biológicas como cáries, periodontite ou peri-implantite são descritas em estudos clínicos com coroas cerâmicas. Neste estudo, o uso da tecnologia de infiltração de um vidro experimental foi testado em restaurações cerâmicas sobre implantes. O objetivo foi avaliar como o processo de gradação de vidro em coroas implantossuportadas de zircônia ultratranslúcida (5Y-PSZ) influencia no prognóstico clínico, quando comparado a coroas implantossuportadas com glaze comercial. Através de critérios préestabelecidos, e após assinatura do termo de consentimento livre e esclarecido, os pacientes foram eleitos para a submissão da cirurgia de instalação de implantes osseointegrados totalizando 57 instalados. Após período de osseointegração, as etapas de reabertura, confecção de provisórias, escaneamento e instalação das coroas sobre implantes parafusados em zircônia foram realizadas. Os pacientes foram randomicamente divididos em dois grupos: Zircônia ultranslúcida e glaze comercial (GC) e zircônia ultratranslúcida e glaze experimental (GE). Os demais grupos são referentes às provisórias (P) e os dentes controles (D). Os desgastes da coroa e do dente antagonista foram analisados através do software GOM Inspect, estabilidade de cor pelo estrofotômetro VITA Easyshade® V, análise imunológica por teste ELISA e as avaliações clínicas e análise do biofilme subgengival foram verificadas por Checkerboard dos grupos GC, GE, P e D nos tempos: fase de provisória (-T), 7 dias após instalação da coroa (T0), 3 meses (T1), 6 meses (T2), 9 meses (T3) e 12 meses (T4) após a entrega. O desgaste não apresentou diferença estatisticamente significativa entre os grupos em todos os intervalos de tempo, indicando desempenho comparável do tratamento (GE) ao glaze (GC) e ao esmalte antagonista (E). Foi observado maior concentração MMP-8 no P do que em D, já para IL-6 essa diferença não foi observada estatisticamente. Em T0 e T1 não houve diferenças significativas na expressão de MMP-8 e IL-6 para os glazes testados. Quando comparado os glazes com o dente, o GC apresentou menor concentração de MMP-8 em T0 e igualou-se ao dente ao passar do tempo (T1). Já o GE se apresentou estatisticamente semelhante ao dente tanto em T0 quanto em T1, também se assemelhando ao GC nos mesmos tempos. Para IL-6 apenas o grupo comercial apresentou aumento em sua concentração ao longo de 6 meses. Para TNF-α não foi possível detectar expressão. Ocorreram episódios de fratura na região cervical em duas coroas do grupo GE, após o T0 e entre os tempos T3 e T4 e uma fratura do componente ti-base entre T2 e T3. Em relação a análise de cor não houve diferença estatística entre os grupos GC e GE em T0 e T1. Em T0 a porcentagem de biofilme foi semelhante entre os glazes testados e ambos significativamente menor quando comparado ao dente. Para T1 nenhuma das coroas teve presença de biofilme supragengival visível. As médias de profundidade a sondagem das coroas se assemelharam entre si, com maior valor estatístico que o dente tanto em T0 quanto em T1. Para altura de tecido queratinizado, GE e GC foram semelhantes assim com a largura da papila distal. Para o Checkerboard em T0 não houve diferença estatística para os grupos GC e GE tanto para prevalência quanto para níveis, já em T1 S. epidermidis apresentou frequência e nível maior em GE do que em GC, Lactobacillus spp apresentou maior frequência em GC do que GE, sendo D semelhante ao GE. Em T2 as cepas Mitis streptococci, Milleri streptococci, Prevotella spp., P. gingivalis, L. buccalis e C. albicans apresentou maior frequência em GE do que GC enquanto T. denticola e Actinomyces spp apresentaram maior frequência em GC do que em GE. A espécie T. socranskii apresentou uma diminuição em sua prevalência para o grupo GC ao longo de 6 meses. Em T2 as cepas Mitis streptococci, Milleri streptococci, L. buccalis, Eubacterium spp., C. albicans, C. difficile apresentaram maior em nível para o grupo GE quando comparado ao GC. Ao longo do tempo (T0-T2) as cepas T. socrasnkii e Lactobacillus spp. aumentaram estatisticamente para o GC. Dessa forma, as coroas de zircônia com infiltração de vidro experimental apresentaram desempenho clínico, biológico e estético comparável ao glaze comercial, sem diferenças significativas quanto ao desgaste, estabilidade de cor ou expressão inicial de citocinas inflamatórias. O GE se comportou semelhante ao dente em diversos parâmetros sem diferença estatística na resposta inflamatória e comportamento de desgaste, enquanto o GC exibiu aumento de IL-6 ao longo do tempo. A microbiota submucosa diferiu entre os tipos de coroas e dente, sendo o grupo experimental mais semelhante aos dentes naturais neste quesito. Houve fraturas em ambos os grupos de zircônia, mas o novo material mostrou comportamento mecânico e microbiológico interessantes, sugerindo que o revestimento e gradação funcional com vidro representam uma alternativa viável para restaurações implantossuportadas melhoradas em zircônia.
Functional grading with experimental glass in zircônia implant-supported crowns: mechanical and biological behavior in a randomized controlled and translacional clinical study
Keywords: Porcelana dentária; Biofilmes; Líquido do sulco gengival; Gingival crevicular fluid; Biofilms; Dental porcelain